Low dose aprotinin increases mortality and morbidity in coronary artery bypass surgery(*) - Sabzi, Feridoun (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: The low dose aprotinin consistently reduces blood and transfusion requirement in adults during cardiac surgical procedures but its effectiveness in some ethnical groups were debated and controversy about its effect on mortality and morbidity precludes its routine use. This study was designated to determine whether a low dose of aprotinin causes more mortality and morbidity when used after coronary artery bypass grafting (CABG) surgery. METHODS: In a clinical trial study, 380 patients in placebo and 273 patients in aprotinin group were enrolled. A test dose before skin incision and 2 million kallikrein inactivation units (KIU) during initiation of cardiopulmonary bypass (CPB) were given to patients. Differences in quantity of blood transfusion, morbidity and mortality were analyzed. Multivariable analysis was performed to determine risk factors for mortality. RESULTS: Decreased blood product transfusions and increased rate of morbidity were found in the aprotinin group. Independent predictors for increased number of transfusion were aspirin continued before operation and small body mass index (BMI) but there was a significant difference in mortality and morbidity between two groups. CONCLUSIONS: In patients undergoing CABG procedure, low dose aprotinin is effective in attenuating post bypass coagulopathy and decreasing blood product use, but it increases morbidity.